Fiber-Optic System for Monitoring Pit Collapse Prevention; Applied Sciences; Vol. 14, iss. 11 - Neshina E. Elena; Mekhtiev A. Ali; Kalitka V. Valery; Kaliaskarov N. B. Nurbol Baltabaevich; Galtseva (Gal’tseva) O. V. Olga Valerievna; Kazambaev I. M. Iljyas Maratuly (2024, 2024)
Title screen